PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING PADA HASIL BELAJAR IPS SISWA KELAS V IPS SD NEGERI 03 SRIKATON KABUPATEN MUSI RAWAS: PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING PADA HASIL BELAJAR IPS - Septi Ayu, Monica (LP3MKIL, 2022)
This study aims to determine learning outcomes in social studies learning for fifth grade students at SD negeri 04 Srikaton after the student facilitator learning model was applied and explained significantly. The research method used is experimental (Pre-experimental Designs) in the form of One Group pre-test and post-test designs. The data collection technique in this research is using a test. As for the steps of the analysis technique, namely, normality test and z test with an avarege value of 87,3 post-test. Based on the z analysis, the obtained z_count = 19,84 > 1,64 so it can be said that the Student facilitator learning model and explaining can complete student learning outcomes in learning Social Studeis class V SD Negeri 04 Srikaton.